Peluang Investasi Saham di Era Pandemi Covid-19 - Komang Fridagustina Adnantara (Jurnal Widya Akuntansi dan Keuangan, 2023)
Covid-19 was announced to enter Indonesia for the first time in early 2020. This immediately had an impact for the Indonesian capital market which fall in various sectors. This can be seen from the Composite Stock Price Index (IHSG) which reached its lowest point at 3,912. However, entering 2021 as the second year of the pandemic era, the IHSG actually increased 10.08% compared to the previous year. This study aims to find out which industrial sectors and stocks have opportunities in the Covid-19 pandemic era throughout 2020 and 2021 in terms of market capitalization. The method used in this research is a literature study. The results of the analysis show that the industrial sector in the capital market that has investment opportunities in the Covid-19 pandemic era, seen from its market capitalization, are companies in the financial industry sector (BBCA, BBRI, BMRI, and BBNI), the consumer goods industry sector (UNVR, HMSP, and ICBP), as well as the telecommunications industry sector (TLKM).